Formulation and evaluation of polyherbal anti-acne patch - Nilofar Khan; Anjali Prabhakar Pawar; Sakshi Patil; Prajakta Ravindra Patil; Payal Vinayak Patil; Prathamesh Navnath Patil; Sweety R. Dalvi; Shubhangi V. Kshirsagar; Mohan Kale (MGM Journal of Medical Sciences)
Background: Herbal anti-acne patches are designed to treat acne and blemishes by reducing breakouts, absorbing excess oil, promoting healing, preventing infection, and reducing pain. They also hydrate the skin, offering convenience and ease of use. These patches aim to effectively target and treat acne lesions, encourage healing, prevent future breakouts, and provide comprehensive care for clearer, healthier skin, all without causing irritation or discomfort. Materials and Methods: In this preparation, fresh marigold flowers were collected, cleaned, dried, powdered, and sifted. Neem leaves were gathered, cleaned, dried, ground, weighed, and stored. Results: The results revealed that the anti-acne patches were evaluated for quality based on moisture content, pH, thickness, absorption, folding resistance, and swelling. Conclusion: The study developed anti-acne patches using ethanol extracts from marigold flowers and neem leaves, known for their antibacterial and antioxidant properties. Effective against Propionibacterium acnes and Staphylococcus aureus, the patches demonstrated significant bacterial inhibition through agar well diffusion and broth microdilution methods, suggesting their potential as safe, natural acne treatments.